Green synthesis of nickel oxide nanoparticles using Allium cepa peels for degradation of Congo red direct dye: an environmental remedial approach - Muhammad Asim Rafique (IWA Publishing, 2021)
Direct dyes are used in different textile operations and processings. The textile industries are disposing of unused direct dyes into the aquatic environment which is posing a serious alarming threat to aquatic lives. The current study deals with the synthesis of nickel oxide nanoparticles using Allium cepa peels aqueous extract. Nickel oxide nanoparticles (NiO-NPs) were characterized by scanning electron microscopy (SEM). Synthesized NiO-NPs were used to remove Congo red direct dye. Various experimental factors like concentration of dye and nanoparticles, pH, and temperature were optimized. Congo red direct dye was decolorized up to 90% at optimized conditions (Congo Red Direct dye concentration 0.02%, catalyst dose 0.003 g·L−1, pH 6, and temperature 50 °C). The real textile industry effluent disclosed 70% decolorization at optimized conditions. The percent reduction in total organic carbon (TOC) and chemical oxygen demand (COD) was found to be 73.24% and 74.56% in the case of Congo red dye catalytic treatment and the percent reduction in TOC and COD was found to be 62.47% and 60.23%, respectively, in the treatment of textile effluent using nickel oxide nanoparticles as a catalyst. Treated and untreated dye samples were exposed to Fourier transform infrared (FTIR) and UV-Visible spectral analyses too. The reaction products were studied by degradation pathway. HIGHLIGHTS Agro-waste material.; Direct dye.; Nickel nanoparticles synthesis.; Application of nanoparticles in dye removal.; Application of optimal conditions on textile effluent.;